Kontribusi Kesehatan Mental Terhadap Daya Tahan Kardiorespirasi Anggota Ukm Floorball Putra Universitas Negeri Surabaya - Nisa, Thobibah Khoirun; Dewi, Ratna Candra; Sudijandoko, Andun; Pudjijuniarto , Pudjijuniarto (Jurnal Porkes, 2025)
This study aims to investigate the relationship and contribution of mental health and cardiorespiratory endurance among male floorball athletes at Surabaya State University. This study will use a quantitative research design, using the DASS21 questionnaire research instrument and the MFT test to collect data. This study has a population of 50 Unesa Male Floorball Athletes. The sample was taken as many as 30 athletes with purposive sampling technique. Data collection techniques and instruments used to measure mental health levels are DASS21 questionnaires. Multi-Stage Fitness Test (MFT) is a research tool that helps collect the necessary data. This study analyzed the data using Statistical Package for Social Science (SPSS) version 25. In this study it was found that there was a very strong relationship between mental health and cardiorespiratory endurance in members of the Surabaya State University men's floorball UKM by 78.2%. In this case the mental health factor contributes 61.2% to the athlete's cardiorespiratory endurance, while the remaining 21.8% is influenced by other factors not examined in this study such as age, gender, athlete nutrition and so on.